Individual security and slavery in the police reports (Brazil, 1840-1880) - de Azevedo, Larissa Biato [UNESP] (Universidad de Antioquia, 2022)
In 19th century Brazil, the development of the police institution made possible the emergence of narratives about practices that offended life and property, among other facts that were happening in the Provinces. This article aims to reflect on the specifics of police daily routine in Brazil from the relationship between individual security and slavery manifested in police reports from the imperial period. It seeks to show how these brief reports emerged and gained space within the scope of the administration of security in the Empire, presenting occurrences in which slaves figured as objects and perpetrators of crimes. It indicates how these facts permeated the history of the police in the country.
Segurança individual e escravidão nos relatos policiais (Brasil, 1840-1880)
Seguridad individual y esclavitud en los informes policiales (Brasil, 1840-1880)
Keywords: Brazil empire; police; slavery; State